Knowledge and Awareness of Osteoporosis: A Survey of Physical Therapy Providers in Saudi Arabia - Muataz Almaddah; Fahad Alzahrani; RiziqAllah Gaowgzeh; Abdullah Alqarni; Rani Othman; Afnan Gmmash (International Journal of Clinical Practice)
Background. Osteoporosis “OP” is classified as one of the most serious health conditions worldwide. OP increases the skeletal fracture risk by 35%, particularly at hip, spine, and wrist joints. Healthcare professionals should be aware of OP clinical signs and have good knowledge while managing all patients. Objectives. This study aims to investigate the current level of osteoporosis knowledge and awareness among physical therapy providers in Saudi Arabia. Methods. One hundred and sixty-eight physical therapy providers participated in this cross-sectional electronic survey from February to July of 2021. The participants completed the Osteoporosis Knowledge Assessment Tool questionnaire (OKAT). Descriptive analysis was utilized to assess the current level of osteoporosis knowledge among physical therapy providers. Results. Among the 168 participants, 55% (n = 92) were over 31 years old and 45% (n = 76) were 30 years old or under. The majority of participants 37% (n = 62) had more than 10 years of experience, 45% (n = 76) mainly treat orthopedic conditions, and 70% (n = 117) live in the western region. The results showed that 67.9% (n = 114) of participants had good knowledge about osteoporosis, while 19.6% (n = 33) had poor knowledge, and only 12.5% (n = 21) had excellent knowledge. Conclusion. Physical therapy providers in Saudi Arabia have a good knowledge of osteoporosis. The overall OP preventive measure knowledge questions were poor. It is crucial for physical therapy providers to act appropriately to prevent falls and mitigate any potential risks.